Analysis of the Steel Plate Shear Wall of Damage Index with pushover Method and Comparing with Special Steel Moment Frame - ghasem pachideh (Iranian Society of Structrual Engineering (ISSE), 2019)
Over the recent years, different damage indices have been to predict the building damage, each of which uses different parameters to model the building damage. In this paper, 27 frames containing 18 frames with lateral load resisting systems of thin-steel shear wall type, as well as 9 frames with lateral load resisting systems of special steel moment frame, on three short (3-story), moderate (7-story) and tall ( 15 floors) height mode have been go under Incremental Load analysis and their failure index has been calculated at different levels of performance for 4 Park and Ang indexes including: maximum relative displacement , framing, and plasticity. The results show that the damage index for the frame with lateral load resisting systems of the steel shear wall in longer frames yields better results than other frames. So the use of this system is more justifiable. In addition, the results show that the maximum relative displacement index has different results than other indexes. Considering the performance levels achieved for short , medium and high-rise buildings, it can be concluded that the existence of two steel shear walls in the building is justified only in high-rise buildings. That is, the minimum number of openings that are responsible for drift of the structure is sufficient for a steel shear wall system, and the use of more openings affects the behavior of the structure and its function